Analisis Yuridis Pendirian Bank Syariah dari Hasil Usaha Berbunga Bank Konvensional - Widya Wahyu Utami; Muhamad Rizki; Faisal Santiago (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
The development of Islamic banking in Indonesia through spin-off mechanisms from conventional banks raises juridical-philosophical issues related to the legality and legitimacy of initial capital sources derived from interest-bearing (riba) businesses. This study aims to comprehensively analyze the establishment of Islamic banks sourced from the interest-bearing profits of conventional banks from the perspective of Indonesian positive law and Islamic law. As comprehensive qualitative research, this study employs a normative juridical method with statutory and conceptual approaches. The results show that from a formal-juridical perspective, the establishment of Islamic banks through spin-offs is permitted by national banking regulations, specifically Law No. 21 of 2008, which places greater emphasis on fulfilling capital and institutional aspects. However, substantively, Islamic law requires a process of separation and purification of assets (tathhir al-mal) to cleanse capital from elements of riba. Without this mechanism, the Islamic legitimacy of the bank becomes fragile, even if its formal legality is met. This study confirms that substantive sharia compliance, which includes the purity of capital sources, is a fundamental prerequisite for maintaining the integrity and public trust in the sharia banking industry in Indonesia.